Tumbuhan Paku di Kucur Watu: Sumber Belajar Digital Keanekaragaman Hayati untuk SMA - Purnamasari, Ita; Sofiyana, Marinda Sari; Sholihah, Mar'atus (Symbiotic: Journal of Biological Education and Science, 2025)
The diversity of fern species represents valuable local biodiversity that can be integrated into biology education as a contextual learning resource. This study aimed to develop and evaluate the feasibility and practicality of an e-catalog on fern diversity in the Blitar area. The research employed a research and development (R&D) design following the Sugiyono model, covering stages from problem identification to product revision. The e-catalog was validated by experts in terms of content, media design, and language, and further assessed for practicality through readability tests involving biology teachers and Grade X students at SMA Negeri 4 Blitar. Validation results indicated high feasibility, with scores of 97% for content, 90.5% for media, and 93.9% for language. The practicality test achieved an average readability score of 88.52%, classified as very practical. These findings demonstrate that the developed e-catalog is pedagogically sound and technologically accessible, serving as an innovative digital learning resource that facilitates independent learning while integrating local biodiversity potential into formal biology education.